Analisis Penerapan Akuntansi Lingkungan terhadap Limbah pada Pabrik Kelapa Sawit (PKS) PT. ATM (Anugrah Tanjung Medan) Kampung Rakyat Labuhan Batu Selatan Sumatera Utara - Lestari, Anugrah Putri (Lembaga Yasin AlSys, 2025)
This study aims to analyze how the company identifies, recognizes, measures, presents, and discloses environmental accounting for waste treatment costs in financial statements. This research is qualitative in nature. The data used in this study at the Palm Oil Mill (PKS) PT. ATM (Anugrah Tanjung Medan) Kampung Rakyat, Labuhan Batu Selatan, North Sumatra, consists of primary and secondary data. Primary data is obtained from interviews, while secondary data is taken from the company's financial reports. The data analysis in this study employs a qualitative descriptive approach by comparing existing regulations with the implementation of environmental accounting at the Palm Oil Mill (PKS) PT. ATM (Anugrah Tanjung Medan) Kampung Rakyat, Labuhan Batu Selatan, North Sumatra. The results indicate that the implementation of environmental accounting at the Palm Oil Mill (PKS) PT. ATM (Anugrah Tanjung Medan) has been successfully carried out. PT. ATM (Anugrah Tanjung Medan), utilizing a checklist technique, has achieved 80% compliance, meaning it adheres to the guidelines, while the remaining 20% does not follow existing norms. PT. ATM (Anugrah Tanjung Medan) only accounts for costs related to liquid and solid waste management. Meanwhile, Susenohaji's regulations cover costs related to product management, non-production material purchases, environmental prevention and management, as well as maintenance and compensation for the impact of waste and emissions. However, in accordance with Susenohaji’s theory, the company has documented its environmental activities.